2013
DOI: 10.1007/s00330-013-2811-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing enhancing from nonenhancing renal masses with dual-source dual-energy CT: iodine quantification versus standard enhancement measurements

Abstract: • Enhancement of renal lesions is important when differentiating benign from malignant tumours. • Dual-energy CT offers measurement of iodine uptake rather than mere enhancement values. • Whole-tumour iodine quantification seems more accurate than standard CT enhancement measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(63 citation statements)
references
References 32 publications
1
58
4
Order By: Relevance
“…13,15 One possible reason might be because the smallest size of renal lesions in our study was 0.5 cm, whereas that of renal lesions in other previous studies was 1 cm 13,15 Our study demonstrated that IO images from the CMP had 11 false-positive cases (size range, 0.5-1.1 cm) and IO images from the LNP had 21 false-positive cases (size range, 0.5-1.4 cm). However, no false-positive cases were found in renal lesions with the size $1.5 cm in differentiating between solid and cystic renal lesions using DECT.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…13,15 One possible reason might be because the smallest size of renal lesions in our study was 0.5 cm, whereas that of renal lesions in other previous studies was 1 cm 13,15 Our study demonstrated that IO images from the CMP had 11 false-positive cases (size range, 0.5-1.1 cm) and IO images from the LNP had 21 false-positive cases (size range, 0.5-1.4 cm). However, no false-positive cases were found in renal lesions with the size $1.5 cm in differentiating between solid and cystic renal lesions using DECT.…”
Section: Discussionmentioning
confidence: 52%
“…Several recent studies have reported the utility of iodine quantification on DECT in distinguishing enhancing from non-enhancing renal lesions. 15,16 Further studies should be performed to evaluate whether this technique is superior to standard enhancement measurement or can overcome the issue of pseudoenhancement in renal cysts. Fifth, we did not perform qualitative analysis for IO and linearly blended images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine image is hypersensitive to the iodine preparation meaning IC can directly indicate the distribution of blood perfusion in lesions. Compared with the conventional CT, IC is a more suitable imaging index for accurately analyzing slightly enhancing lesions [17-20]. IC has been applied for evaluating the effectiveness of anti-tumor treatment including hepatocellular carcinoma, gastric stromal tumor, and non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ascenti et al [60] demonstrated that spectral-based dual-energy CT iodine quantification is more accurate than standard enhancement measurements in distinguishing enhancing from non-enhancing renal masses , especially in depicting minimally enhancing neoplasms, such as papillary RCC and/or in excluding enhancement in small renal cysts (Figs. 3.15 and 3.16).…”
Section: Spectral Ct: Study Protocols and Clinical Applicationsmentioning
confidence: 97%